Aristóteles y Tomás de Aquino en torno al tratamiento de la materia moral - de Blassi, Martín (Sapientia, 2014)
This paper aims to specify doctrinal differences between Aristotle and Thomas Aquinas on the topic of moral behaviour. It will study this matter through an analytical and descriptive search accompanied by an interpretative and critical reading of sources and specialized bibliography. This point allows to understand how Aquinas takes over the aristotelian knowledge about human good, and how He resolves various paradoxes that presents the same approach.